Happy birthday, Kit! : a springtime story, 1934 - Tripp, Valerie, 1951- (American girls collection., 2001)
On a visit to Cincinnati from rural Kentucky during the Great Depression, Aunt Millie impresses Kit with her money-saving cleverness. Includes information on life in America during the Great Depression.